2018
DOI: 10.1111/jgs.15611
|View full text |Cite
|
Sign up to set email alerts
|

Weak Grip Strength and Cognition Predict Functional Limitation in Older Europeans

Abstract: Objectives To estimate the effects of baseline grip strength and cognition on the trajectory of functional limitation over time. Design Longitudinal study of older adults participating in the Survey of Health, Ageing and Retirement in Europe (SHARE). Setting Urban and rural households in 11 European countries and Israel. Participants Individuals aged 50 and older from SHARE (2004–2015) (N=14,073; 52.5% female). Measurements Outcomes were functional limitation scores from five panel wave. Main exposure variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
1
21
2
Order By: Relevance
“…Our findings are similar to those of previous studies, which demonstrated that GS could predict cognition over time (Stijntjes et al, 2016; Jeong and Kim, 2018; Wang et al, 2019), for instance, Veronese et al (2016) found that lower handgrip strength could predict incident cognitive decline in a population of 1,249 elderly community dwellers over a period of 4.4 years. However, there were studies that reported results contrary to our findings, for example, a 6-year follow-up study by Atkinson et al (2010) revealed that there was no significant association between physical performance (such as gait, balance, and GS) and cognitive changes in 1,793 elderly women.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to those of previous studies, which demonstrated that GS could predict cognition over time (Stijntjes et al, 2016; Jeong and Kim, 2018; Wang et al, 2019), for instance, Veronese et al (2016) found that lower handgrip strength could predict incident cognitive decline in a population of 1,249 elderly community dwellers over a period of 4.4 years. However, there were studies that reported results contrary to our findings, for example, a 6-year follow-up study by Atkinson et al (2010) revealed that there was no significant association between physical performance (such as gait, balance, and GS) and cognitive changes in 1,793 elderly women.…”
Section: Discussionsupporting
confidence: 92%
“…The World Health Organization reports that developing and maintaining functional ability that enables an individual's dignity and well-being in older age represents a top priority for healthy aging. 1 However, functional limitation, a substantial impairment in a person's ability to effectively perform main daily tasks (such as mobility and personal hygiene), [2][3][4] is still an increasingly common experience in later life and becomes a significant public health concern worldwide. Extensive studies have documented negative consequences associated with functional limitation, such as depression, 5 cognitive impairment, 6 reduced quality of life, 7 increased health care use and cost, 8,9 and morbidity and mortality, [10][11][12] which can impose a heavy burden on families and society.…”
Section: Introductionmentioning
confidence: 99%
“…Decaffeinated coffee contains many non-caffeine compounds, such as chlorogenic acid and diterpenoids. Chlorogenic acid, as the most common compounds, improves many aspects of cognition such as sustained attention, reaction time and alertness (29) ; those ability was essential for older adults to maintain their physical function (30) . Therefore, the beneficial effects of decaffeinated coffee might be partially due to chlorogenic acid which enhanced sustained attention and reaction time.…”
Section: Discussionmentioning
confidence: 99%